Effectiveness And Usability Evaluation Study Of IVR System In Multimedia University, Cyberjaya - Chin, Chua Chin (2004)
The paper presents a usability and effectiveness evaluation study of the implemented IVR system application in Multimedia University Cyberjaya - MMU InfoLine. The usability and effectiveness study of the system will be done concurrently as both are correlated.